Studying the local character of Raman features of single-walled carbon nanotubes along a bundle using TERS - Peica, Niculina (Springer, 2011)
Here, we show that the Raman intensity of the G-mode in tip-enhanced Raman spectroscopy (TERS) is strongly dependent on the height of the bundle. Moreover, using TERS we are able to position different single-walled carbon nanotubes along a bundle, by correlating the observed radial breathing mode (RBM) with the AFM topography at the measuring point. The frequency of the G(- )mode behaves differently in TERS as compared to far-field Raman. Using the RBM frequency, the diameters of the tubes were calculated and a very good agreement with the G(-)-mode frequency was observed.